Political power and social theory. Vol. 15 - Davis, Diane E., 1953- (Amsterdam ; London : JAI, 2002)
Volume 15 offers a series of critical articles and commentaries by some of the leading historically-oriented social scientists writing in academia today. Collectively, the articles examine issues ranging from the relations between class, power and history, to the role of states and culture in mediating those dynamics. Special attention is paid to race, gender, citizenship and civil society in the formation of such structures and processes. The countries or regions under study include the United States, Brazil, Chile, China, Mexico, Samoa and Southwest Africa. In keeping with the journal's commitment to inter-disciplinary, as well as historical inquiry, our nine contributors come from a variety of disciplines (sociology, political science, anthropology and history), all drawing on debates and themes that cut across the social sciences. The significance of the inter-disciplinary perspective is seen not only in the range of cases, literatures and methodologies brought to bear on the key issues under study; it also forms the substantive core of several contributions that call for a rethinking of conventional disciplinary boundaries and methodological frames.
Description based on print version record.
Keywords: Power (Social sciences); Political sociology; Social sciences -- Philosophy; Political science & theory; Political Science -- General